Analysis Of Voice Quality on Aircraft Telephone Through Internet Telephony Gateway in Voice Over Internet Protocol - Muthoharo Muthoharo; Martono Dwi Atmadja; Abdul rasyid (Jurnal Jaringan Telekomunikasi, 2022)
Along with the development of the era, analog telephones have been replaced by IP Phones whose communication range can be wider and more flexible. Therefore, analog telephones are almost forgotten because of the limited communication range. With the addition of ITG (Internet Telephony Gateway) then analog telephones can communicate in VoIP networks. This research will discuss the analysis of voice quality in the communication process between telephone sets via ITG in a VoIP network based on the shape of the input and output, the amplitude response to frequency changes and the delay. Data retrieval is done by using a transmission test set as a substitute for human voice and knowing the amplitude value generated every time there is a change in frequency and an oscilloscope as a tool to determine the shape of the input and output waves as well as the delay. The results of this study indicate that delay generated by communication between analog telephones is <1 ms. When viewed from the form of the information signal generated from communication between telephone sets, that is, the shape of the input and output information signals are both sines, so it can be said that the information signal has not decreased in quality. The amplitude response resulting from frequency changes in communication between analog telephones is, the greater the value of the communication frequency.